Artefacts of legal inquiry : the value of imagination in adjudication - Del Mar, Maksymilian, 1979- (Oxford ; Hart Publishing, 2020)
"What is the value of fictions, metaphors, figures and scenarios in adjudication? This book develops three models to help answer that question: inquiry, artefacts and imagination. Legal language, it is argued, contains artefacts - forms that signal their own artifice and call upon us to do things with them and thanks to them. To imagine, in turn, is to enter a distinctive epistemic frame where we temporarily suspend certain epistemic norms and commitments and participate actively along a spectrum of affective, sensory and kinetic involvement. The book argues that artefacts and related processes of imagination are valuable insofar as they enable inquiry in adjudication, i.e. the social (interactive and collective) process of making insight into what values, vulnerabilities and interests might be at stake in a case and in cases like it in the future. The book is structured in two parts, with the first offering an account of the three models of inquiry, artefacts and imagination, and the second examining four case studies (fictions, metaphors, figures and scenarios). Drawing on a broad range of theoretical traditions - including philosophy of imagination and emotion, the theory and history of rhetoric, and the cognitive humanities - this book offers an interdisciplinary defence of the importance of artefactual language and imagination in adjudication"--
Introduction -- Inquiry -- Artefacts -- Imagination -- Enabling Inquiry -- Fictions -- Metaphors -- Figures -- Scenarios -- Conclusion.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Description based on online resource; title from digital title page (viewed on March 11, 2020).
Keywords: Law -- Language; Law -- Methodology; Jurisprudence & philosophy of law; Electronic books